The Middle Pivot Element Algorithm. (31st December 2012) - Kumari, Anchala; Chakraborty, Soubhik
Abstract : This paper is an improvement over the previous work on New Sorting Algorithm first proposed by Sundararajan and Chakraborty (2007). Here we have taken the pivot element as the middle element of the array. We call this improved version Middle Pivot Element Algorithm (MPA) and it is found that MPA is much faster than the two algorithms RPA (Random Pivot element Algorithm) and FPA (First Pivot element Algorithm) in which the pivot element was selected either randomly or as the first element, respectively.